QUANTIFICATION OF DIAGENESIS IN CENOZOIC SHARKS: ELEMENTAL AND MINERALOGICAL CHANGES - Labs-Hochstein J.; MacFadden B.J. (My University, 2006)
Diagenesis of bone during fossilization is pervasive, however, the extent of this process varies with depositional environment. This study quantifies diagenesis of shark vertebral centra through analysis of a suite of physical and chemical characters including crystallinty index (CI), carbonate content, and elemental concentrations. Although shark skeletons are initially cartilaginous, the soft cartilage of the vertebral centra is replaced with carbonate hydroxyapatite during growth. Nine vertebral centra are analyzed from lamnoid (Lamnoidea) sharks ranging in age from the cretaceous to recent using Fourier transform infrared spectroscopy (FT-IR) and inductively coupled plasma mass spectrometry (ICPMS). The variables CI, carbonate content, rare earth element (REE) concentrations, Ca/P, Ba/Ca, Sr/Ba, (La/Yb)N, (La/Y)N, (La/Yb)N vs. (La/Sm)N, La/Yb, and Ce anomalies elucidate the diagenetic and depositional environments of the seven fossil vertebral centra. The two extant centra demonstrate the initial, unaltered end-member conditions for these variables. Two fossil vertebral centra (Carcharodon megalodon and Isurus hastalis) demonstrate a strong terrestrial influence during diagenesis (distinctive flattening of shale-normalized REE patterns) that masked the seawater signal. Three centra (Carcharodon auriculatus, Carcharodon angustidens, and Creotxyrhina mantelli) have indications of some terrestrial influx evident by some flattening of the REE patterns relative to seawater. The terrestrial influence in these five shark centra (C. megalodon, I. hastalis, C. auriculatus, C. angustidens and C. mantelli) are interpreted to represent a primarily nearshore habitat for these species. In contrast, the two Otodus obliquus centra have REE patterns that represent the original seawater signal and have no indications of terrigenous input. These results indicate that fossil shark vertebral centra have the potential to understand diagenesis and reconstruct paleooceanographic environments.
Keywords: BONE; CARBONATE GROUP; CENOZOIC; DEPOSITIONAL ENVIRONMENT; DIAGENESIS; FISH; FOSSIL RECORD; FOSSILIZATION; FTIR SPECTROSCOPY; INDUCTIVELY COUPLED PLASMA METHOD; PALEOCEANOGRAPHY; CARCHARODON; CHONDRICHTHYES; ISURUS; OTODUS OBLIQUUS; Cenozoic